2016
DOI: 10.14744/anatoljcardiol.2016.7248
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 5-lipoxygenase by zileuton in a rat model of myocardial infarction

Abstract: Objective:The goal of the present study was to investigate the effects of 5-lipoxygenase (5-LOX) inhibition, alone and with cyclooxygenase (COX) inhibitors, on inflammatory parameters and apoptosis in ischemia/reperfusion (I/R)-induced myocardial damage in rats. For this purpose, zileuton, a selective and potent inhibitor of 5-LOX, resulting in suppression leukotriene production, was used.Methods:Male Wistar rats (200-250 g; n=12 per group) were used in the study. I/R was performed by occluding the left corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Recently, a study reported the cardioprotective effects of zileuton, namely, good protective effects against H 2 O 2 -induced oxidative stress and cell damage in both cardiac myogenic H9c2 cells, and neonatal rat cardiomyocytes (NRCMs) were found [8]. Zileuton has been reported to protect against myocardial infarction injury in a rat model [9]. Zileuton was also found to inhibit the development of pulmonary hypertension in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study reported the cardioprotective effects of zileuton, namely, good protective effects against H 2 O 2 -induced oxidative stress and cell damage in both cardiac myogenic H9c2 cells, and neonatal rat cardiomyocytes (NRCMs) were found [8]. Zileuton has been reported to protect against myocardial infarction injury in a rat model [9]. Zileuton was also found to inhibit the development of pulmonary hypertension in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that Zileuton reduces apoptosis and relieves inflammatory events in various models [ 6 , 26 , 27 ]. Consistent with those findings, we observed that Zileuton suppressed pro-apoptotic transcriptional changes (increased expression of BAX and decreased expression of Bcl2) induced by SAH as well as the corresponding increase in the incidence of apoptotic (TUNEL-positive) cells.…”
Section: Discussionmentioning
confidence: 99%
“…An in situ cell death detection peroxidase (POD) kit (Roche Diagnostics, Mannheim, Germany) was used for the TUNEL technique and the sections were stained according to the manufacturer's protocol. In each sampling frame, a counting area was designated without bias and the apoptotic index was calculated by dividing the apoptotic (TUNEL-positive) RGC number by the total RGC number [19]. TUNEL-positive RGCs were counted by the same investigator (UU) blinded to the group assignment.…”
Section: Tunel Assay and Apoptotic Indexmentioning
confidence: 99%